2021
DOI: 10.3390/ijms22136774
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Blood-Derived Endometrial Stem Cells’ Impact for the Treatment Perspective of Female Infertility

Abstract: When looking for the causes and treatments of infertility, much attention is paid to one of the reproductive tissues—the endometrium. Therefore, endometrial stem cells are an attractive target for infertility studies in women of unexplained origin. Menstrual blood stem cells (MenSCs) are morphologically and functionally similar to cells derived directly from the endometrium; with dual expression of mesenchymal and embryonic cell markers, they proliferate and regenerate better than bone marrow mesenchymal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The extent of trophoblast invasion relies on communication between the placenta and maternal decidua. Studies have demonstrated increased decidualization markers such as IGFBP1 and prolactin in endometrial stromal cells after hormonal treatment [ 35 , 36 ]. Moreover, endometrial stromal cells of women with a history of PE failed to decidualize in vitro after hormonal treatment [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of trophoblast invasion relies on communication between the placenta and maternal decidua. Studies have demonstrated increased decidualization markers such as IGFBP1 and prolactin in endometrial stromal cells after hormonal treatment [ 35 , 36 ]. Moreover, endometrial stromal cells of women with a history of PE failed to decidualize in vitro after hormonal treatment [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study reports that another therapeutic mechanism to prevent ovarian failure is to inhibit granulosa cells apoptosis, human placenta-derived mesenchymal stem cells (hPMSCs) can inhibit granulosa cells apoptosis by modulating stress levels controlled by the IRE1-a pathway [ 29 ]. One of the newest therapeutic approaches is to use stem cells extracted from human menstrual blood [ 30 ]. And the successful engraftment of mesenchymal stem cells was transplanted into the ovaries of cyclophosphamide (CTX)-induced POI model mice [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease is often associated with cigarette smoking exposure. Chen and co-workers studied the protective effects of adipose-derived stem cell-conditioned medium (ADSC-CM) against cigarette-smoke-extract-induced cell death and epithelial–mesenchymal transition (EMT) on human lung cancer and non-cancerous epithelial cells model [ 11 ]. ADSC-CM effectively inhibited EMT induced by cigarette smoke extract and was able to reverse the gradual loss of epithelial marker expression associated with TGF-β1 treatment.…”
Section: Solid Organs Dysfunction and Mscs Secretomementioning
confidence: 99%
“…Studies performed by Navakauskiene’s research group are focused on endometrial stem cells as an attractive target for studies on infertility of unexplained origin in women [ 11 ]. Menstrual-blood-origin stem cells are morphologically and functionally similar to cells derived from the endometrium.…”
Section: Biological and Functional Assessment Of Mscs And Secretomementioning
confidence: 99%
See 1 more Smart Citation